2015
DOI: 10.1155/2015/376576
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 5‐Amyno‐4‐(1,3‐benzothyazol‐2‐yn)‐1‐(3‐methoxyphenyl)‐1,2‐dihydro‐3H‐pyrrol‐3‐one Intake on Digestive System in a Rat Model of Colon Cancer

Abstract: Introduction. Pyrrol derivate 5-amyno-4-(1,3-benzothyazol-2-yn)-1-(3-methoxyphenyl)-1,2-dihydro-3H-pyrrol-3-one (D1) has shown antiproliferative activities in vitro, so investigation of the impact of D1 intake on gut organs in rats that experienced colon cancer seems to be necessary. Materials and Methods. D1 at the dose of 2.3 mg/kg was administered per os daily for 27 (from the 1st day of experiment) or 7 (from the 21st week of experiment) weeks to rats that experienced 1,2-dimethylhydrazine (DMH)-induced co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, we demonstrated that every investigated compound did not cause the changes in C and G of model membranes which could be interpreted as destructive ones. Taking into account the similar effects of 2a…2e on model membranes and low toxicity of 2a (Kuznietsova et al 2013(Kuznietsova et al , 2015 we might suggest low toxicity of all the investigated compounds. At the same time, observed changes let us to conclude the ability of 2a…2e to intercalate into the membrane and therefore probably to react with intramembrane or submembrane domains of the receptors, such as those with protein kinase activity.…”
Section: Biological Assaysmentioning
confidence: 81%
See 1 more Smart Citation
“…Furthermore, we demonstrated that every investigated compound did not cause the changes in C and G of model membranes which could be interpreted as destructive ones. Taking into account the similar effects of 2a…2e on model membranes and low toxicity of 2a (Kuznietsova et al 2013(Kuznietsova et al , 2015 we might suggest low toxicity of all the investigated compounds. At the same time, observed changes let us to conclude the ability of 2a…2e to intercalate into the membrane and therefore probably to react with intramembrane or submembrane domains of the receptors, such as those with protein kinase activity.…”
Section: Biological Assaysmentioning
confidence: 81%
“…The panel of 1-(4-R-benzyl)-3-R1-4-(R2phenylamino)-1H-pyrrole-2,5-diones were synthesized and tested on antiproliferative activity. Among them 3-chloro-1-(4-chlorobenzyl)-4-((3-(trifluoromethyl)phenyl)amino)-1H-pyrrole-2,5-dione 2a (Table 1) demonstrated the ability to inhibit colon cancer cell lines HCT-116, SW-620, Colo-205 (GI 50 approximately 1.0-1.6 × 10 −8 M) (Dubinina et al 2007;Garmanchuk et al 2013a) and colonic tumors growth on rat chemically induced colon cancer model (Kuznietsova et al 2013;Garmanchuk et al 2013b), Furthermore, compound 2a reveals antioxidant properties (Kuznietsova et al 2016) and low toxicity (Kuznietsova et al 2015), so could be considered the promise basis for targeted antitumor drug development.…”
Section: Introductionmentioning
confidence: 99%
“…The MI-1 also demonstrated the anti-inflammatory activity [25]. The anti-cancer activity of the MI-1 was shown in the in vitro [24,[26][27][28] and in vivo experiments [29][30][31][32]. However, poor water solubility remains a big drawback of the biomedical application of the MI-1 that hinders its application as a medicinal remedy.…”
Section: Introductionmentioning
confidence: 99%
“…In order to approve the anticancer action in vitro of the created complex of MI-1 immobilized on the poly (PEGMA-co-DMM) carrier, a set of experiments aimed at the investigation of cellular and molecular mechanisms of the antineoplastic action of this complex were conducted with targeting human colon carcinoma cells of HCT116 line. The main reason of such selection of cells was based on the results of our former studies which demonstrated high effectiveness of the MI-1 in treatment of disorders of gastro-intestinal tract (e.g., inflammation) [24,25,29,30]. Here, we found that the immobilization of the MI-1 on the carrier poly (PEGMA-co-DMM) provided a creation of a water-soluble form of MI-1, and also enhanced the antineoplastic action in vitro of the MI-1.…”
Section: Introductionmentioning
confidence: 99%